2015
DOI: 10.3892/ijo.2015.3109
|View full text |Cite
|
Sign up to set email alerts
|

Increased urothelial cancer associated 1 is associated with tumor proliferation and metastasis and predicts poor prognosis in colorectal cancer

Abstract: Long non-coding RNA, urothelial cancer associated 1 (UCA1), is reported to play a critical role in progression of carcinogenesis. In the present study, we identified differential expression of UCA1 in colorectal cancer (CRC) and paired peritumoral tissues using gene expression microarray analyses. qPCR analysis confirmed that UCA1 was upregulated in CRC (p<0.001) and the expression of UCA1 was statistically correlated with lymph node metastasis (P=0.040), distant metastasis (P=0.043) and tumor stage (P=0.010).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 40 publications
0
61
1
Order By: Relevance
“…21 Increased UCA1 was associated with tumor proliferation and metastasis and predicted poor prognosis in CRC. 22 In this study, we found that UCA1 was overexpressed in RCC tissues compared with the adjacent normal tissues, and higher expression levels of UCA1 were associated with advanced tumor stage.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…21 Increased UCA1 was associated with tumor proliferation and metastasis and predicted poor prognosis in CRC. 22 In this study, we found that UCA1 was overexpressed in RCC tissues compared with the adjacent normal tissues, and higher expression levels of UCA1 were associated with advanced tumor stage.…”
Section: Discussionmentioning
confidence: 69%
“…21 Increased UCA1 was associated with tumor proliferation and metastasis and predicted poor prognosis in CRC. 22 In this study, we found that UCA1 was overexpressed in RCC tissues compared with the adjacent normal tissues, and higher expression levels of UCA1 were associated with advanced tumor stage.Numerous studies suggest that UCA1 play critical roles in some cancer development and progression. Wang et al 23 found that upregulation of UCA1 contributed to progression …”
mentioning
confidence: 69%
“…Dozens of lncRNAs are reported to be potential biomarkers for cancer diagnosis and prognosis prediction in many solid tumors (8,9). Recently, LncRNA-H19, UCA1 and HOTAIR were also reported strongly correlated with CRC metastasis and prognosis (12)(13)(14). Therefore, lncRNAs are believed to represent a new category of cancer biomarkers and potential tumor therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…We previously identified aberrant expression of lncRNAs between CRC and matched paratumor normal tissues by a microarray analysis (13). Briefly, we selected six pairs of CRC tissues and corresponding paratumor normal tissues and assayed the expression of lncRNAs (30,586 items) and protein-coding mRNAs (26,109 items).…”
Section: Introductionmentioning
confidence: 99%
“…UCA1 is highly expressed in diverse cancer types, such as breast cancer (17), pancreatic cancer (18), gastric cancer (19), and colorectal cancer (20,21), suggesting that high expression of UCA1 might serve as a molecular marker for predicting metastasis and prognosis in these cancers (22). Several studies also demonstrated that upregulation of UCA1 is associated with EMT in breast cancer (23) and bladder cancer (24), but the underlying mechanism remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%